Development of rhabdomyolysis in a child after norovirus gastroenteritis. Issue 1 (December 2016) - Nishio, Tomohiro; Yonetani, Ryoko; Ito, Eisuke; Yoneta, Makiko; Maruo, Yoshihiro; Yoshida, Tokiko; Sugimoto, Tohru
Abstract Background In children, the most significant cause of rhabdomyolysis or muscle breakdown is viral infection. However, there are no reports that norovirus, a gastroenteric virus that commonly infects children, specifically causes rhabdomyolysis. Here, we report the first pediatric case of norovirus-associated rhabdomyolysis. Case presentation The patient, a 2-year-old boy with fever, diarrhea, and vomiting, was referred to our hospital with dysstasia and transaminitis. He was diagnosed with rhabdomyolysis. Additionally, norovirus genogroup GII was detected from stool samples by real-time quantitative reverse transcription Polymerase Chain Reaction, and thereafter, the norovirus GII.4 variant was identified. Conclusion However, the association between rhabdomyolysis and the isolated norovirus variant was not clarified. After treatment the patient recovered without renal failure or disseminated intravascular coagulation. Rhabdomyolysis is a disease for which there is a need for early detection and treatment. If abnormal posture or muscle weakness is observed during the course of gastroenteritis, blood and urinary tests should be performed to rule out rhabdomyolysis.